2018
DOI: 10.1016/j.cub.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Contributions of Mesencephalic Locomotor Region Nuclei to Locomotor Control in the Freely Behaving Mouse

Abstract: The mesencephalic locomotor region (MLR) has been initially identified as a supraspinal center capable of initiating and modulating locomotion. Whereas its functional contribution to locomotion has been widely documented throughout the phylogeny from the lamprey to humans, there is still debate about its exact organization. Combining kinematic and electrophysiological recordings in mouse genetics, our study reveals that glutamatergic neurons of the cuneiform nucleus initiate locomotion and induce running gaits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
240
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(273 citation statements)
references
References 77 publications
25
240
0
Order By: Relevance
“…In their recent work, Caggiano et al [2] and Josset et al [3] further explored the anatomical and molecular heterogeneity of the mesencephalic locomotor region, highlighting the differential role of glutamatergic and cholinergic neurons within the cuneiform and pedunculopontine nuclei. They found that glutamatergic cuneiform nucleus neurons were able to drive the full range of locomotor gaits — walk, trot, bound and gallop — and speed.…”
Section: Heterogeneity Of the Mesencephalic Locomotor Regionmentioning
confidence: 99%
See 4 more Smart Citations
“…In their recent work, Caggiano et al [2] and Josset et al [3] further explored the anatomical and molecular heterogeneity of the mesencephalic locomotor region, highlighting the differential role of glutamatergic and cholinergic neurons within the cuneiform and pedunculopontine nuclei. They found that glutamatergic cuneiform nucleus neurons were able to drive the full range of locomotor gaits — walk, trot, bound and gallop — and speed.…”
Section: Heterogeneity Of the Mesencephalic Locomotor Regionmentioning
confidence: 99%
“…To better understand how the mesencephalic locomotor region drives movement, Josset et al [3] took a closer look at muscle activity in resting or freely behaving mice following optogenetic activation of excitatory neurons within the cuneiform and pedunculopontine nuclei. The elicited muscle activity patterns were strongly dependent on whether the mouse was resting or walking (state-dependent), the step cycle phase (spinal gating of descending input) and the duration of photostimulation (temporal dynamics of neuronal recruitment).…”
Section: Mesencephalic Locomotor Region Heterogeneity Diversifies Thementioning
confidence: 99%
See 3 more Smart Citations